2011
DOI: 10.1007/s12011-011-9104-z
|View full text |Cite
|
Sign up to set email alerts
|

Trace Elements and Heavy Metals in Hair of Stage III Breast Cancer Patients

Abstract: This prospective study was designed to compare the hair levels of 36 elements in 52 patients with stage III breast cancer to those of an equal number of healthy individuals. Principal component and cluster analysis were used for source of identification and apportionment of heavy metals and trace elements in these two groups. A higher average level of iron was found in samples from patients while controls had higher levels of calcium. Both patients and controls had elevated levels of tin, magnesium, zinc, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 28 publications
1
30
1
1
Order By: Relevance
“…However, recent work has found women with dermatofibromas are much more likely to have breast cancer and that dermatofibromas from breast cancer patients have 2.4-fold more tissue arsenic than those from control in a small study (Dantzig 2009). Breast cancer patients have significantly higher arsenic levels in hair compared with controls in two other studies (Benderli Cihan et al 2011; Joo et al 2009). In a small case-control study, Polish women with a BRCA1 mutation (cases) had a significantly higher risk for breast cancer based on higher serum arsenic levels (Muszynska et al 2012).…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, recent work has found women with dermatofibromas are much more likely to have breast cancer and that dermatofibromas from breast cancer patients have 2.4-fold more tissue arsenic than those from control in a small study (Dantzig 2009). Breast cancer patients have significantly higher arsenic levels in hair compared with controls in two other studies (Benderli Cihan et al 2011; Joo et al 2009). In a small case-control study, Polish women with a BRCA1 mutation (cases) had a significantly higher risk for breast cancer based on higher serum arsenic levels (Muszynska et al 2012).…”
Section: Introductionmentioning
confidence: 70%
“…Recent studies indicate that arsenic may act as an endocrine disruptor (Bodwell et al 2006; Bodwell et al 2004), interfering with the estrogen signaling (Tokar et al 2010a; Waalkes et al 2004; Waalkes et al 2007) or even the expression of ER (Davey et al 2007; Du et al 2012; Shen et al 2007; Waalkes et al 2004). Some studies implicate a potential contribution of this metalloid to breast cancer development (Benderli Cihan et al 2011; Dantzig 2009; Joo et al 2009). However, there are no adequate epidemiological studies showing a firm association between arsenic exposure and an elevated risk of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Antimony is a toxic chemical element naturally occurring in the surface of the earth and is currently used in flame retardants and brake linings of motor cars [42]. One small case-control study (n = 52 cases and 52 controls) reported statistically higher levels of antimony in hair of stage III breast cancer patients compared with healthy controls [43]. In a different case-control study including women with malignant breast cancer (n = 33), benign breast disease (n = 36), and healthy controls (n = 35), Sb levels were higher in the scalp hair of the benign group, and malignant group compared with the controls; however, levels were considerably higher in women with benign lesions [35].…”
Section: Discussionmentioning
confidence: 99%
“…There were 13 studies including 978 exposed cases and 1279 controls ( Figure 1) (Antila et al, 1996;Ionescu et al, 2006;McElroy et al, 2006;Wu et al, 2006;Pasha et al, 2008;Strumylaite et al, 2008;Gallagher et al, 2010;Benderli Cihan et al, 2011;Saleh et al, 2011;Strumylaite et al, 2011;Kotsopoulos et al, 2012;Nagata et al, 2013). The characterization of all selected studies was summarized in Table 1.…”
Section: Meta-analysismentioning
confidence: 99%